Hinduism and law : an introduction - Lubin, Timothy, 1964-; Davis, Donald R., 1970-; Krishnan, Jayanth (New York : Cambridge University Press, 2010)
"Covering the earliest Sanskrit rulebooks through to the codification of 'Hindu law' in modern times, this interdisciplinary volume examines the interactions between Hinduism and the law. The authors present the major transformations to India's legal system in both the colonial and post colonial periods and their relation to recent changes in Hinduism. Thematic studies show how law and Hinduism relate and interact in areas such as ritual, logic, politics, and literature, offering a broad coverage of South Asia's contributions to religion and law at the intersection of society, politics and culture. In doing so, the authors build on previous treatments of Hindu law as a purely text-based tradition, and in the process, provide a fascinating account of an often neglected social and political history"--
Machine generated contents note: Foreword; List of contributors; Chronology; Map; Introduction Timothy Lubin, Donald R. Davis, Jr and Jayanth Krishnan; Part I. Hindu Law: 1. An historical overview of Hindu law Donald R. Davis, Jr; 2. Dharma|s|astra: a textual history Patrick Olivelle; 3. Hindu legal practice in premodern India Axel Michaels; 4. The creation of Anglo-Hindu law Rosane Rocher; 5. Marriage and family in colonial Hindu law Rachel Sturman; 6. Hindu law as personal law Rina Verma Williams; Part II. Law in Ancient and Medieval Hindu Traditions: 7. Hindu jurisprudence and scriptural hermeneutics Lawrence McCrea; 8. Indic conceptions of authority Timothy Lubin; 9. |S|udra Dharma and legal treatments of caste Ananya Vajpeyi; 10. Law, literature, and the problem of politics in medieval India Whitney Cox; 11. Hindu law as performance: ritual and poetic elements in Dharma|s|astra Robert Yelle; Part III. Law and Modern Hinduism: 12. Temples, deities, and the law Richard Davis; 13. In the divine court of appeals: vows before the God of justice Aditya Malik; 14. Contemporary caste discrimination and affirmative action Laura Dudley Jenkins; 15. Law and Hindu nationalist movements Smita Narula; 16. Law and the Hindu Diaspora: a thumbnail survey Jayanth Krishnan; Appendices; Glossary; Bibliography
Includes bibliographical references (p. 271-297) and index.
Keywords: Hindu Law; Hindu law -- History -- Sources; Law -- India -- History; Hinduism